The Oxidative Injury of Extracellular Hemoglobin Is Associated With Reactive Oxygen Species Generation of Grass Carp (Ctenopharyngodon idella) - Qin, Zhendong; Yang, Minxuan; Lu, Zhijie; Babu, V. Sarath; Li, Yanan; Shi, Fei; Zhan, Fanbin; Liu, Chun; Li, Jun; Lin, Li (Frontiers in Immunology, 2022)
Intravascular hemolysis is a fundamental feature of hemorrhagic venereal infection or tissue, and releases the endogenous damage-associated molecular pattern hemoglobin (Hb) into the plasma or tissues, results in systemic inflammation, vasomotor dysfunction, thrombophilia and proliferative vasculopathy. However, how the cytotoxic Hb affects the tissues of grass carp remains unclear. Here, we established a hemolysis module in grass carp by injected phenylhydrazine (PHZ). The data revealed that the hemolysis increased the content of Hb in plasma and activated the antioxidant system. The histopathology analysis data showed that the PHZ induced hemolysis increased the Hb and iron accumulation both in head and middle kidney, which also up-regulated the expression of HO-1. The qRT-PCR detection results suggested that the hemolysis activated the expression of iron metabolism-related genes. Followed, immunofluorescence and immunohistochemistry data revealed that the hemolysis caused an obviously deposition of collagen fiber, MDA and 4-HNE accumulation, and also increased the content of the oxidative-related enzymes including β- GAL, LPO and MDA in both head and middle kidney. Furthermore, the PHZ-induced hemolysis significantly increased the ROS production, which resulted in apoptosis in both in head and middle kidney. Finally, qRT-PCR determination data showed that the hemolysis modulated the expression of cytokine-related genes. Taken together, excess of Hb released from hemolysis causes tissues oxidative damage, which may associate with reactive oxygen species (ROS) and inflammation generation.